PENGARUH MOTIVASI, KOMPETENSI MANAJERIAL, DAN LINGKUNGAN KERJA TERHADAP KINERJA GURU MELALUI DISIPLIN KERJA (STUDI KASUS DI YAYASAN PENDIDIKAN SMP dan SMA BUDI MULIA JAKARTA-BOGOR) - Sigalingging, Riwan; Supriyadi, Edy; Putriana, Lies (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2019)
The objective of this research is to determine the effect of motivation, managerial competence, and work environment on teacher performance through work discipline. Data was collected by questionaire. Data consists of motivation, manajerial competence, and work environment on teacher performance through work discipline. The techniques data collection by census approach. The results showed that motivation, managerial competence, and work environment influence teacher performance through work discipline. Managerial competence can motivate which influences teacher performance through work discipline. A work environment which is too comfortable makes teacher less motivated. Motivation, managerial competence and work environment can effect teacher performance through work discipline in SMP dan SMA Budi Mulia Jakarta-Bogor. Keywords: Motivation, Managerial competence, work environment and teacher performance through work discipline.